Selection played a role in the evolution of the human chin. Issue 82 (May 2015) - Pampush, James D.
Abstract: Chins, which are unique to humans, have generated considerable debate concerning their evolutionary origins, yet a consensus has remained elusive. Many have argued that chins are adaptations for chewing stress, speech, or sexual ornamentation. Alternatively, some have suggested that chins are spandrels—byproducts of selection operating elsewhere in the mandible or face. Lastly, chins could be the product of genetic drift. The questions addressed by this study are: [1] whether chins represent an exceptionally derived morphological condition, and [2] if this can be interpreted as the product of natural selection. These questions are important since the chin is one of the features used to define Homo sapiens in the fossil record. Quantitative measures that capture the degree of chin expression were gathered from a sample of 123 primate taxa, and evolutionary rates associated with these measures were reconstructed in the primate phylogeny. The evolutionary rate associated with these measures was reconstructed to be far higher along the Homo tip (∼77 times greater than the primate background rate of evolution) than elsewhere in the primate phylogeny. These results suggest that human symphyseal morphology is exceptionally derived relative to other primates, and selection has been operational in producing the human chin.